Anterior cervical discectomy and fusion versus anterior cervical corpectomy and fusion in multilevel cervical spondylotic myelopathy: A meta-analysis. Issue 49 (December 2016) - Wang, Tao; Wang, Hui; Liu, Sen; An, Huang-Da; Liu, Huan; Ding, Wen-Yuan
Abstract: Background: Both anterior cervical discectomy and fusion (ACDF) and anterior cervical corpectomy and fusion (ACCF) are used to treat multilevel cervical spondylotic myelopathy (mCSM); however, which one is better treatment for mCSM remains considerable controversy. A meta-analysis was performed to compare clinical outcomes, radiographic outcomes, and surgical outcomes between ACDF and ACCF in treatment for mCSM. Methods: An extensive search of literature was performed in Pubmed/MEDLINE, Embase, the Cochrane library, CNKI, and WANFANG databases on ACDF versus ACCF treatment for mCSM from January 2011 to August 2016. The following variables were extracted: length of hospital stay, blood loss, operation time, Japanese Orthopedic Association (JOA) scores, Neck Disability Index (NDI) score, fusion rate, Cobb angles of C2 to C7, dysphagia, hoarseness, C5 palsy, infection, cerebral fluid leakage, donor site pain, epidural hematoma, graft subsidence, graft dislodgment, pseudoarthrosis, and total complications. Data analysis was conducted with RevMan 5.3 and STATA 12.0. Results: A total of 8 studies containing 878 patients were included in our study. The results showed that ACDF is better than ACCF in the angle of C2 to C7 at the final follow-up ( P  < 0.00001, standardized mean difference = 4.76 [3.48, 6.03]; heterogeneity: P = 0.17, I 2 = 43%), C5 plasy ( P = 0.02, odds ratio [OR] 0.42, 95% confidence interval [CI] 0.21, 0.86; heterogeneity: P = 0.52, I 2 = 0%), blood loss ( P  < 0.00001, standardized mean difference = −53.12, 95% CI −64.61, −41.64; heterogeneity: P = 0.29, I 2 = 20%), fusion rate ( P = 0.04, OR 2.54, 95% CI 1.05, 6.11; heterogeneity: P = 0.29, I 2 = 20%), graft subsidence ( P = 0.004, OR 0.11, 95% CI 0.02, 0.48; heterogeneity: P = 0.94, I 2 = 0%), and total complications ( P = 0.0009, OR 0.56, 95% CI 0.40, 0.79; heterogeneity: P = 0.29, I 2 = 18%).However, there are no significant differences in length of hospital stay, operation time, JOA scores, NDI scores, preoperative angle of C2 to C7, dysphagia, hoarseness, infection, cerebral fluid leakage, donor site pain, epidural hematoma, graft dislodgment, and pseudoarthrosis (all P  > 0.05). Conclusions: Based on our meta-analysis, our results suggest that both ACDF and ACCF are good plans in clinical outcomes; however, ACDF is a better choice in radiographic outcomes and total complications for the treatment of multilevel CSM.